Pelatihan Mengidentifikasi Cacat Produk Pada UMKM El-Fariza - Awliya, Lisa Salwa; Nayla, Putri; Surachman, Richa (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
El-Fariza MSMEs that sell Muslim clothing face various problems related to product quality, such as loose buttons and zippers and torn fabrics. This study aims to identify the source of product defects and provide effective solutions. The methods used include in-depth interviews with employees to understand training needs and analysis using fishbone diagrams to find the root of the problem. The results of the analysis show that product defects are caused by human factors, methods, materials, machines and measurements. As a solution, it is recommended to provide training to employees on proper sewing techniques and selection of quality materials. In addition, the implementation of a double-checking system and Standard Operating Procedures (SOPs) is also recommended to improve production quality. These measures are expected to improve customer satisfaction and the competitiveness of MSMEs in the market. This service makes a significant contribution to quality management in the MSME sector and offers a model that can be applied by other businesses. By implementing an efficient quality control system, MSMEs can reduce waste and improve their image in the eyes of consumers.